Point-of-care ultrasound (POCUS) as a key tool in the diagnosis of pheochromocytoma: a case report in an elderly patient with extreme blood pressure variability - Nati-Castillo, H. A.; Saavedra T., Jhan S.; Valderrama, Luis Alfonso; Ortiz-Prado, Esteban; Izquierdo-Condoy, Juan S. (Frontiers in Medicine, 2025)
BackgroundPheochromocytoma is a rare, life-threatening, neuroendocrine tumor originating from catecholamine-secreting chromaffin cells, with an incidence of up to 8 per million people globally each year. It manifests a broad spectrum of symptoms due to excessive catecholamine secretion, often mimicking other conditions and complicating its diagnosis. Its clinical variability poses a significant diagnostic challenge, delaying appropriate interventions–particularly in resource-limited settings.Case presentationWe report the case of a 73-years-old male who arrived at the emergency department exhibiting chest pain, palpitations, marked blood pressure fluctuations without clinical signs of tachycardia, and excessive sweating, initially suggesting a potential coronary event. Initial cardiac evaluations, including coronary angiography, were inconclusive. The application of readily available Point-of-Care Ultrasound (POCUS) provided crucial initial insights, prompting further abdominal imaging. This imaging revealed a left adrenal mass indicative of pheochromocytoma, which was subsequently confirmed through computed tomography (CT) scanning. The patient underwent urgent adrenalectomy, resulting in the stabilization of his symptoms and blood pressure levels. Histopathological analysis confirmed the diagnosis.ConclusionThis case underscores the critical role of POCUS in the emergency setting, where hypotension and hypertension may signal a high-risk scenario requiring urgent diagnosis. POCUS can significantly enhance diagnostic accuracy and influence patient outcomes. Its use can expedite the identification of pheochromocytoma and improve management strategies, particularly in settings with limited access to advanced imaging.